The anthropometric history of Native Americans, c. 1820 - 1890 - John Komlos; Leonard Carlson (Center for Economic Studies and ifo Institute (CESifo), 2012)
The trend of the height of Indian scouts in the U.S. Army born between ca. 1825 and 1875 is analyzed. Their average height of ca. 170 cm (67 in.) confirms that natives were tall compared to Europeans but were nearly the shortest among the rural populations in the New World. The trend in their height describes a slightly inverted U shape with an increase between those born 1820-34 and 1835-39 of ca. 1.8 cm (0.7 in.) (p=0.000) and a subsequent slight decline after the Civil War. This implies that they were able to maintain and perhaps even improve their nutritional status through the Civil War, though harder times followed for those born thereafter. We also recalculate the heights of Native Americans in the Boas sample and find that the Plains Indians were shorter than most rural Americans. The trend in the height of Indians in the Boas sample is similar to that of the Scouts.
Keywords: N00; 330; Native Americans; Indians; anthropometric history; height; physical stature; biological standard of living; Indianer; Indigene Völker; Anthropologie; Ernährung; USA